Biogenic terbium oxide nanoparticles as the vanguard against osteosarcoma - Iram, Sana; Khan, Salman; Ansary, Abu Ayoobul; Arshad, Mohd; Siddiqui, Sahabjada; Ahmad, Ejaz; Khan, Rizwan H.; Khan, Mohd Sajid (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2016)
The synthesis of inner transition metal nanoparticles via an ecofriendly route is quite difficult. This study, for the first time, reports synthesis of terbium oxide nanoparticles using fungus, Fusarium oxysporum. The biocompatible terbium oxide nanoparticles (Tb2O3 NPs) were synthesized by incubating Tb4O7 with the biomass of fungus F. oxysporum. Multiple physical characterization techniques, such as UV-visible and photoluminescence spectroscopy, TEM, SAED, and zeta-potential were used to confirm the synthesis, purity, optical and surface characteristics, crystallinity, size, shape, distribution, and stability of the nanoemulsion of Tb2O3 NPs. The Tb2O3 NPs were found to inhibit the propagation of MG-63 and Saos-2 cell-lines (IC50 value of 0.102 mu g/mL) and remained non-toxic up to a concentration of 0373 gg/mL toward primary osteoblasts. Cell viability decreased in a concentration-dependent manner upon exposure to 10 nmTb(2)O(3) NPs in the concentration range 0.023-0373 mu g/mL Cell toxicity was evaluated by observing changes in cell morphology, cell viability, oxidative stress parameters, and FACS analysis. Morphological examinations of cells revealed cell shrinkage, nuclear condensation, and formation of apoptotic bodies. The level of ROS within the cells an indicator of oxidative stress was significantly increased. The induction of apoptosis at concentrations <= IC50 was corroborated by 4',6-diamidino-2-phenylindole dihydrochloride (DAPI) staining (DNA damage and nuclear fragmentation). Flow-cytometric studies indicated that the response was dose dependent with a threshold effect. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Biosynthesis; Cytotoxicity; fusarium oxysporum; Osteosarcoma; Tb2O3 nanoparticles